Zeolitic Imidazolate Framework-8 Nanoparticles Exhibit More Severe Toxicity to the Embryo/Larvae of Zebrafish (Danio rerio) When Co-Exposed with Cetylpyridinium Chloride - Xuchun Qiu; Lei Liu; Wei Xu; Chen Chen; Ming Li; Yanhong Shi; Xiangyang Wu; Kun Chen; Chongchen Wang (MDPI AG, 2022)
The combined application of nanoparticles and surfactants has attracted tremendous attention in basic research and industry. However, knowledge of their combined toxicity remains scarce. In this study, we exposed zebrafish embryos to cetylpyridinium chloride (CPC, a cationic surfactant, at 0 and 20 μg/L), zeolitic imidazolate framework nanoparticles (ZIF-NPs, at 0, 30, and 60 mg/L), and their mixtures until 120 h post-fertilization (hpf). Within the used concentration range, both single and combined exposures exhibited limited effects on the survival and hatching of zebrafish. However, the combined exposure of ZIF-NPs and CPC caused more severe effects on the heart rate at both 48 and 72 hpf. The combined exposure also induced significant hyperactivity (i.e., increasing the average swimming velocity) and oxidative stress in zebrafish larvae (at 120 hpf), although all single exposure treatments exhibited limited impacts. Furthermore, the level of reactive oxygen species (or malondialdehyde) exhibited a significantly positive correlation with the heart rate (or average swimming velocity) of zebrafish, suggesting that oxidative stress plays a role in mediating the combined toxicity of CPC and ZIF-NPs to zebrafish. Our findings suggest that the interaction of CPC and ZIF-NPs should not be ignored when assessing the potential risks of their mixtures.